Productive Innovation and Technology Transfer Center Design to reduce Technological Gaps in agro-export companies in Lambayeque Department (LACCEI, 2024)
The word Technology Gap refers to the difference between the technologies that a company has and the technologies that it could have. This gap can manifest itself in several aspects, such as the efficiency of business processes, the ability to compete with other companies or the ability to adapt to market changes, based on this, this research is proposed with the general objective to reduce the Technological Gaps in agro-export companies in the Department of Lambayeque through the design of a Center for Productive Innovation and Technology Transfer. It began with the diagnosis, applying a survey of 47 questions to the sample of Managers, or administrators or managers of the Research + Development + Innovation Areas of 66 companies that are part of the population of 125 agro-export companies Secondly, the proposal for a Center for Productive Innovation and Agroindustrial Technology Transfer was prepared, prioritizing the trend of value-added products in the international market, and sizing the plant based on the mass balance of raw materials to be served per day, and using the Guerchet methodology for calculating areas, all under the regulations in force by the Technological Institute of Production, which is the entity responsible in Peru for the creation and operation of the so-called CITEs Finally, the profitability of the proposal was evaluated under a social approach, resulting in an IRR of 10.14% and a NPV of S/ 2,280,785, declaring the proposal viable. The study concludes that the design of a public CITE for the Lambayeque agro-export sector contributes positively and sustainably to closing technological gaps in productive infrastructure, laboratory analysis, technical assistance for quality assurance and specialized training in innovation.